2016
DOI: 10.1093/nar/gkw1184
|View full text |Cite
|
Sign up to set email alerts
|

MAX is an epigenetic sensor of 5-carboxylcytosine and is altered in multiple myeloma

Abstract: The oncogenic transcription factor MYC and its binding partner MAX regulate gene expression by binding to DNA at enhancer-box (E-box) elements 5΄-CACGTG-3΄. In mammalian genomes, the central E-box CpG has the potential to be methylated at the 5-position of cytosine (5mC), or to undergo further oxidation to the 5-hydroxymethyl (5hmC), 5-formyl (5fC), or 5-carboxyl (5caC) forms. We find that MAX exhibits the greatest affinity for a 5caC or unmodified C-containing E-box, and much reduced affinities for the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 67 publications
1
85
0
Order By: Relevance
“…Pioneer transcription factors that are not sensitive to DNA modifications or nucleosome occupancy may be able to bind to these sites and recruit TET proteins to generate oxi-mC (Figure 1), with subsequent effects on other transcription factor binding such as basic helix-loop-helix (bHLH) family members binding E-box sites. Some E-box motifs contain a CpG and hemi-modified sequences containing C on one strand and 5caC on the other augmented the TF/DNA interaction [30]. At CpG containing sites, DNA containing symmetrical 5mC or 5hmC modifications impaired binding, while hemi-modified sequences were permitted [30,31].…”
Section: Tet Proteins During Natural Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pioneer transcription factors that are not sensitive to DNA modifications or nucleosome occupancy may be able to bind to these sites and recruit TET proteins to generate oxi-mC (Figure 1), with subsequent effects on other transcription factor binding such as basic helix-loop-helix (bHLH) family members binding E-box sites. Some E-box motifs contain a CpG and hemi-modified sequences containing C on one strand and 5caC on the other augmented the TF/DNA interaction [30]. At CpG containing sites, DNA containing symmetrical 5mC or 5hmC modifications impaired binding, while hemi-modified sequences were permitted [30,31].…”
Section: Tet Proteins During Natural Differentiationmentioning
confidence: 99%
“…Some E-box motifs contain a CpG and hemi-modified sequences containing C on one strand and 5caC on the other augmented the TF/DNA interaction [30]. At CpG containing sites, DNA containing symmetrical 5mC or 5hmC modifications impaired binding, while hemi-modified sequences were permitted [30,31]. In this scenario, a single base modification followed by DNA replication could allow binding at this site in both daughter cells.…”
Section: Tet Proteins During Natural Differentiationmentioning
confidence: 99%
“…It is also possible that different proteins/factors recognize the modifications and determine their fate [43]. Interestingly, some recent experiments demonstrated that transcription factors, Myc and Max, and perhaps also a number of other regulatory proteins, may specifically recognize 5-caCyt, but have lesser affinity to 5-fCyt, and show only a trace of affinity to 5-mCyt and 5-hmCyt [44]. Moreover, a recent study conducted by Xiong et al [45] showed that Sall4, an oncogenic protein being overexpressed in colon cancer [46], may further enhance TET2-catalyzed oxidation of 5-hmCyt.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the MYC binding partner MAX (a basic helix‐loop‐helix protein) has been shown to bind its CpG‐containing enhancer target DNA sequence preferentially in the presence of a caC or C rather then mC, hmC or fC. A crystal structural analysis of MAX bound to its caC‐containing target DNA revealed a critical arginine involved in recognition of the caC‐paired G residue and a second arginine in ∼6 Å distance to the caC carboxyl group that may be involved in water‐mediated interactions with this group …”
Section: Interactions Of Natural Dna Binding Protein Scaffolds With mentioning
confidence: 99%